Portrait of Gender and Development in Village Area, do They Shape Inclusivity? - Ika Arinia Indriyany; Moh Rizky Godjali (Journal of Governance, 2023)
The existence of women in the village realm is a dilemmatic phenomenon. On the one hand, female leaders can demonstrate the breaking down of stigma and stereotypes that women will not appropriately fill the public sphere. On the other hand, their existence is no different from formality, ignoring the substance and representation of women's interests. This research seeks to compare three villages that were and are currently led by women. Do they reflect inclusiveness? This inclusiveness from the campaign period to the dynamics when taking office will be seen. The research results show that not all female leaders at the village level can design inclusiveness. In carrying out village development planning deliberations, for example, women's involvement is more to overcome administrative requirements than to accommodate their interests.